Current concepts and controversies in the management of early stage Hodgkin lymphoma - Maeda, Lauren S. (Leuk Lymphoma, 2011)
Over the past three decades, due to the recognition of late effects related to high-dose extended field radiotherapy and heavy alkylator chemotherapy, combined modality therapy with abbreviated chemotherapy and limited field radiotherapy has emerged as the standard of care for early stage Hodgkin lymphoma, with cure rates in excess of 80%. Currently, however, controversy remains over identifying the most appropriate criteria to risk-stratify patients with early stage disease, so that those with a favorable prognosis receive limited treatment without compromising cure rates and those with unfavorable risk receive more intensified therapy. The optimal risk stratification system remains unclear, with variable definitions of favorable and unfavorable disease used by research groups in North America and Europe. Thus, comparison of clinical trial results has been challenging, and additional controversies persist regarding optimal chemotherapy regimens, duration of therapy, and the role of radiotherapy. Investigations are ongoing to assess the potential of functional imaging and biomarkers as tools for risk stratification. The collective goal is to further refine current stratification strategies to allow for an individualized, risk-adapted treatment approach that minimizes long-term late effects without compromising high cure rates.